2015
DOI: 10.1186/s12888-015-0500-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment by client and case manager for shared decision making in outpatient forensic psychiatry

Abstract: BackgroundIn outpatient forensic psychiatry, assessment of re-offending risk and treatment needs by case managers may be hampered by an incomplete view of client functioning. The client’s appreciation of his own problem behaviour is not systematically used for these purposes. The current study tests whether using a new client self-appraisal risk assessment instrument, based on the Short Term Assessment of Risk and Treatability (START), improves the assessment of re-offending risk and can support shared decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Similar results were found byvan den Brink et al (2015) who sampled 201 outpatient forensic mental health service users and their case managers and assessed patient-staff concordance on key risk and protective factors appearing on the Short Term Assessment of Risk and Treatability (START;Webster, Martin, Brink, Nicholls, & Desmarais, 2009). While agreement was good at the service user and staff group levels, the level of concordance between individual patient and case manager pairs was poor.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Similar results were found byvan den Brink et al (2015) who sampled 201 outpatient forensic mental health service users and their case managers and assessed patient-staff concordance on key risk and protective factors appearing on the Short Term Assessment of Risk and Treatability (START;Webster, Martin, Brink, Nicholls, & Desmarais, 2009). While agreement was good at the service user and staff group levels, the level of concordance between individual patient and case manager pairs was poor.…”
supporting
confidence: 53%
“…Perhaps the most significant advance in this respect has been the promotion of shared decision-making (SDM) models (e.g., Barker, 2012;van den Brink et al, 2015). Although these models have been advanced primarily in general psychiatry (Drake, Cimpean, & Torrey, 2009;Hamann, Leucht, & Kissling, 2003) and in relation to medical treatment decisions (Joosten et al, 2008), their applicability to risk assessments in forensic mental health is increasingly recognised (Barnao, Ward, & Robertson, 2016;Coffey, 2012;Dixon, 2012;Sullivan, 2005).…”
Section: Risk Assessment and Management Within The Recovery Modelmentioning
confidence: 99%
“…Whether this is specific for clinicians working in an outpatient setting remains to be tested. Inviting clients to assess their own risk and protective factors for violence and to select their own 'key' factors may be helpful here, both to involve them in shared care planning and to improve the predictive value of violence risk assessment (van den Brink et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, these features may have therapeutic significance, such as drawing attention to positive aspects of client functioning and fostering the therapeutic alliance and patient motivation for treatment, which are without a doubt worthwhile considerations in the clinical application of risk assessment. However, these therapeutic claims require testing Troquete et al, 2013;van den Brink et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Shared decision making for care planning has demonstrated that it improves risk management and patient satisfaction in outpatient settings [32][33][34]. As READY creates a shared platform by integrating data from both patients and physicians, the influence of technology on physician and patient interactions may become either an obstacle or the enabler of physicians' use of technology [35].…”
Section: Shared Decision Making Using a Mobile App In Outpatient Settmentioning
confidence: 99%